Work hardening of non-axisymmetric die-less spinning - Jia, Zhen (Strojniški vestnik, 2017)
Non-axisymmetric shell parts are widely used in the fields of aviation, aerospace and automobiles. Because of good flexibility, short production preparation period and low cost, die-less spinning has the advantages in processing those parts. However, the special work-hardening distribution being caused by its processing technology will affect the performance of these parts. Therefore, the work-hardening of non- axisymmetric die-less spinning is studied through experiments and by using the finite element method (FEM). The law of smaller half cone angle (HCA) with bigger work-hardening is found by testing the surface hardness of the spun workpieces. Microstructure observation and theoretical analyses are adopted to reveal the law. The reason for that is that the roller causes greater plastic strain inhomogeneity in the smaller HCA-forming process. It is also found that the working condition with the largest HCA difference has the biggest work-hardening difference and the maximum hardness difference can be 15 %.
Keywords: finite element method; metoda končnih elementov; napetosti; osno nesimetrično rotacijsko preoblikovanje; rotacijsko preoblikovanje brez trna; stanje preoblikovalnega utrjanja